Pulse-width control scheme for fixed-frequency ZVS DC-DC converter with active auxiliary circuit - Jabbar A.F.; Mansor M.; Rahim N.A. (IEEE Computer Society, 2023)
Today's technology in microprocessors has significantly improved as operation above Mhz range for microcontroller and digital signal processing (DSP) are easy to obtain and inexpensive to own. Since reactive components such as transformers, capacitors, and inductors are frequency dependent devices, using higher frequency will significantly reduce the component size. This leads to many developments of smaller converters with higher power density at cheaper cost. However, these advantages are limited by the present of hard-switching loss. Hard-switching loss is undesirable because it leads to higher power loss, excessive heat, and electromagnetic interference (EMI). To overcome these problems, researchers have developed soft-switching techniques which are capable of eliminating hard-switching loss. This paper presents a study of active auxiliary circuit with zero-voltage-switching (ZVS) in a 500W DC-DC full bridge converter. Simulation base experiment will be conducted at variant input source and different load conditions. 2013 IEEE.